Likes Me, Likes Me Not - Stine, Megan; Series Created by Griffard, Robert and Adler, Howard (London Harper, 2003)
Meet Mary-Kate and Ashley, the Tween Queen Twins! Your new best friends have just arrived...
Keywords: Twins -- Two of a kind (Television program)